2002
DOI: 10.1128/jvi.76.8.3765-3773.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hantavirus Genetic Diversity in Argentina: S Segment-Derived Phylogeny

Abstract: Nucleotide sequences were determined for the complete S genome segments of the six distinct hantavirus genotypes from Argentina and for two cell culture-isolated Andes virus strains from Chile. Phylogenetic analysis indicates that, although divergent from each other, all Argentinian hantavirus genotypes group together and form a novel phylogenetic clade with the Andes virus. The previously characterized South American hantaviruses Laguna Negra virus and Rio Mamore virus make up another clade that originates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
13

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 45 publications
3
39
0
13
Order By: Relevance
“…Also note that ANDV, CHOV, and MAPV are principally associated with Oligoryzomys species, BCCV, MULV, and CADV are principally associated with Sigmodon species, and-as indicated previously-BAYV is principally associated with Oryzomys palustris. 7,8,10,14,16,17,28,[41][42][43] The results of the NJ analysis of uncorrected p model distances generated from the alignment of N protein amino acid sequences, the MP analysis of the alignment of N protein gene sequences, and the MP analysis of the alignment of N protein amino acid sequences were essentially the same as the results of the NJ analysis of uncorrected p model distances generated from the alignment of N protein gene sequences.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Also note that ANDV, CHOV, and MAPV are principally associated with Oligoryzomys species, BCCV, MULV, and CADV are principally associated with Sigmodon species, and-as indicated previously-BAYV is principally associated with Oryzomys palustris. 7,8,10,14,16,17,28,[41][42][43] The results of the NJ analysis of uncorrected p model distances generated from the alignment of N protein amino acid sequences, the MP analysis of the alignment of N protein gene sequences, and the MP analysis of the alignment of N protein amino acid sequences were essentially the same as the results of the NJ analysis of uncorrected p model distances generated from the alignment of N protein gene sequences.…”
Section: Resultssupporting
confidence: 50%
“…Evidence for this ancient virus-host relationship includes the association of phylogenetically closely related hantaviral species with phylogenetically closely related rodent species, for example-SNV with P. maniculatus and NYV with P. leucopus, [49][50][51] and ANDV, CHOV and MAPV, and RIOMV with Oligoryzomys longicaudatus (long-tailed colilargo), 10,42,43 Oligoryzomys fulvescens (fulvous colilargo), 7,17 and Oligoryzomys microtis (small-eared colilargo), 18 respectively. The results of analyses of cytochrome b gene sequences in an earlier study indicated that Oryzomys species are phylogenetically more closely related to Oligoryzomys species than to Sigmodon species.…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms seem most likely. First, if phylogenetically related host species tend to live sympatrically, then viruses will tend to jump between closely related host species, which appears to be the case for the hantaviruses (2). If this process occurs at sufficient frequency, then the host and virus trees may often match, giving a false impression of cospeciation.…”
Section: ϫ5mentioning
confidence: 99%
“…A similar situation is apparent with the New World hantaviruses (family Bunyaviridae) and the arenaviruses, for which host and virus trees have been compared in detail. In most cases, it seems that these viruses have undergone cospeciation with their murid rodent hosts over several million years, although there is also evidence for occasional cross-species transfers (2,3,26,31). Moreover, a history of cospeciation is not restricted to animal viruses and has also been proposed for the plant tobamoviruses (17).…”
mentioning
confidence: 99%
“…Diverse hantavirus genotypes have been reported to occur throughout a vast geographical range in southern South America (8,35); these include five different lineages of ANDV that have been proposed and named according to their geographic origin in Argentina and Chile (43). These viral genotypes include the following: ANDV Central Plata (ANDV Cent Plata) found on both sides of the Rio de la Plata (in Uruguay and Argentina) and central Buenos Aires province in Argentina; ANDV Central Buenos Aires (ANDV Cent Bs.As.)…”
mentioning
confidence: 99%